Magnetic resonance semiotics of prostate cancer according to the PI-RADS classification. The clinical diagnostic algorithm of a study - A. S. Korobkin; M. A. Shariya; A. S. Chaban; G. A. Voskanyan; A. Z. Vinarov (Вестник рентгенологии и радиологии, 2016)
Objective: to elaborate the magnetic resonance imaging (MRI) signs of prostate cancer (PC) in accordance with the PIRADS classification during multiparametric MRI (mpMRI).Material and methods. A total of 89 men aged 20 to 82 years were examined. A control group consisted of 8 (9%) healthy volunteers younger than 30 years of age with no  urological history to obtain control images and MRI plots and 20 (22.5%) men aged 26–76 years, whose morphological changes were inflammatory and hyperplastic. The second age-matched group included 61 (68.5%) patients diagnosed with prostate cancer at morphological examination. A set of studies included digital rectal examination, serum prostate-specific antigen, and transrectal ultrasoundguided prostate biopsy. All the patients underwent prostate mpMRI applying a 3.0 T Achieva MRI scanner (Philips, the etherlands).Results. The patients have been found to have mpMRI signs that were typical of PC; its  MRI semiotics according to the PI-RADS classification is presented. Each mpMRI rocedure has been determined to be of importance and informative value in detecting PC.Conclusion. The comprehensive mpMRI approach to diagnosing PC improves the quality and diagnostic value of prostate MRI.